2009
DOI: 10.1073/pnas.0810086106
|View full text |Cite
|
Sign up to set email alerts
|

Impaired attentional selection following lesions to human pulvinar: Evidence for homology between human and monkey

Abstract: We examined the contributions of the human pulvinar to goal directed selection of visual targets in 3 patients with chronic, unilateral lesions involving topographic maps in the ventral pulvinar. Observers completed 2 psychophysical tasks in which they discriminated the orientation of a lateralized target grating in the presence of vertically-aligned distracters. In experiment 1, where distracter contrast was varied while target contrast remained constant, the patients' contralesional contrast thresholds for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 47 publications
10
113
1
Order By: Relevance
“…These connections further support our claim regarding the central involvement of sub-cortical regions such as the pulvinar nuclei in spatial attention bias. In line with our findings, neuro-imaging studies suggest that the pulvinar nucleus is related to serial search (Fairhall et al, 2009), covert shifts of attention (Nobre et al, 1997), and attentional selection (Snow et al, 2009). Moreover, lesion studies in humans showed the critical role of the pulvinar in engagement of attention (Rafal and Posner, 1987), spatial and temporal components of feature binding (Arend et al, 2008), and visual search (Ward and Arend, 2007).…”
Section: The Role Of Sub-cortical Structures In Intact Spatial Attentionsupporting
confidence: 90%
“…These connections further support our claim regarding the central involvement of sub-cortical regions such as the pulvinar nuclei in spatial attention bias. In line with our findings, neuro-imaging studies suggest that the pulvinar nucleus is related to serial search (Fairhall et al, 2009), covert shifts of attention (Nobre et al, 1997), and attentional selection (Snow et al, 2009). Moreover, lesion studies in humans showed the critical role of the pulvinar in engagement of attention (Rafal and Posner, 1987), spatial and temporal components of feature binding (Arend et al, 2008), and visual search (Ward and Arend, 2007).…”
Section: The Role Of Sub-cortical Structures In Intact Spatial Attentionsupporting
confidence: 90%
“…Haaker et al, 2014;Vervliet et al, 2013a). In this context it is tempting to speculate that significant activation of thalamic and occipital regions, as observed for generalized RI, may reflect generally facilitated salience processing of incoming information (thalamus: Robinson and Petersen, 1992;Snow et al, 2009;primary visual areas: Khayat et al, 2006), which may support a contribution of non-associative processes to generalized RI. Interestingly a significant correlation between peak parameter estimates and SCR responses, as a measure related to arousal, was only observed for thalamic activations.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the pulvinar nucleus is involved in the modulation of the physical saliency of a stimulus in both humans and non-humans primates (Snow et al, 2009; and recruited for covert forms of goal-directed searches (Fairhall et al, 2009). ROI 8 and 9 showed a more pronounced pattern of sensorimotor connectivity.…”
Section: Ale Profiles Of Each Roi and Functional Clustersmentioning
confidence: 99%